CGRP-dependent signalling pathways involved in mouse models of GTN- cilostazol- and levcromakalim-induced migraine. (December 2021) - Christensen, Sarah L; Rasmussen, Rikke H; Ernstsen, Charlotte; La Cour, Sanne; David, Arthur; Chaker, Jade; Haanes, Kristian A; Christensen, Søren T; Olesen, Jes; Kristensen, David M
Background: Knowledge of exact signalling events during migraine attacks is lacking. Various substances are known to trigger migraine attacks in patients and calcitonin gene-related peptide antagonising drugs are effective against migraine pain. Here, we investigated the signalling pathways involved in three different mouse models of provoked migraine and relate them to calcitonin gene-related peptide and other migraine-relevant targets. Methods: In vivo mouse models of glyceryl trinitrate-, cilostazol- and levcromakalim-induced migraine were applied utilising tactile sensitivity to von Frey filaments as measuring readout. Signalling pathways involved in the three models were dissected by use of specific knockout mice and chemical inhibitors. In vivo results were supported by ex vivo wire myograph experiments measuring arterial dilatory responses and ex vivo calcitonin gene-related peptide release from trigeminal ganglion and trigeminal nucleus caudalis from mice. Results: Glyceryl trinitrate-induced hypersensitivity was dependent on both prostaglandins and transient receptor potential cation channel, subfamily A, member 1, whereas cilostazol- and levcromakalim-induced hypersensitivity were independent of both. All three migraine triggers activated calcitonin gene-related peptide signalling, as both receptor antagonism and antibody neutralisation of calcitonin gene-related peptide were effective inhibitors of hypersensitivity in all three models. Stimulation of trigeminal ganglia and brain stem tissue samples with cilostazol and levcromakalim did not result in release of calcitonin gene-related peptide, and vasodilation following levcromakalim stimulation was independent of CGRP receptor antagonism. Conclusion: The mouse models of glyceryl trinitrate-, cilostazol- and levcromakalim- induced migraine all involve calcitonin gene-related peptide signalling in a complex interplay between different cell/tissue types. These models are useful in the study of migraine mechanisms.